Menguasai Etika Digital : Pengaruh Kontrol Diri, Kelekatan Teman sebaya, dan Kecerdasan Emosional terhadap Etiket Berinternet (Netiket) Melalui Paparan Media Sosial pada Remaja - Aisyah Puspita Putri; Nurjanah Purnama; Putri Fildza Andini; Yulina Eva Riany (Jurnal Ilmu Sosial dan Humaniora, 2024)
The use of social media in the daily lives of adolescents is inevitable. The behavior in the virtual space also needs to be considered so that it does not have a negative impact on others. Internet Etiquette (Netiquette) is a set of social norms in cyberspace that all users need to apply. This study analyzes the influence of self-control, peer attachment, and emotional intelligence on netiquette through social media exposure in adolescents. Two hundred and thirty-seven (237) adolescents aged 10-24 from 21 provinces in Indonesia participated in this online survey. Researchers used five questionnaires and analyzed them using SEM with SmartPLS. The results showed an influence of emotional intelligence, self-control, and social media exposure on the application of teenage netiquette. Emotional intelligence has the highest influence on the application of netiquette. On the other hand, peer attachment indirectly affects netiquette with the mediator variable of social media exposure. It is essential to promote an understanding of netiquette to adolescents as one of the foundations of digital literacy.